2012
DOI: 10.1007/s10803-012-1637-2
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Variation in Health Service Use and Associated Expenditures Among Children with Autism

Abstract: This study examined differences by age in service use and associated expenditures during 2005 for Medicaid-enrolled children with autism spectrum disorders. Aging was associated with significantly higher use and costs for restrictive, institution-based care and lower use and costs for community-based therapeutic services. Total expenditures increased by 5 % with each year of age; by 23 % between 3–5 and 6–11 year olds, 23 % between 6–11 and 12–16, and 14 % between 12–16 and 17–20 year olds. Use of and expendit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
90
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(101 citation statements)
references
References 39 publications
8
90
0
Order By: Relevance
“…This pattern of results is consistent with prior research reporting greater outpatient expenditures among younger versus older youth with an ASD in the Medicaid program (Cidav et al 2013). Among younger children, the most sizeable case-control differences in the adjusted comparisons were observed for speech therapy, occupational/social skills therapy, and physical therapy.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This pattern of results is consistent with prior research reporting greater outpatient expenditures among younger versus older youth with an ASD in the Medicaid program (Cidav et al 2013). Among younger children, the most sizeable case-control differences in the adjusted comparisons were observed for speech therapy, occupational/social skills therapy, and physical therapy.…”
Section: Discussionsupporting
confidence: 90%
“…Analyses were conducted separately for younger (age 3–9; n = 43,170) and older (age 10–17; n=48,350) youth because prior research using Medicaid claims data indicates that patterns of health care utilization among youth with an ASD are distinct at different stages of development (Cidav et al 2013). Less than one percent of each sample was missing information on area-level income (age 3–9: n = 221; age 10–17: n = 244); these individuals were excluded from regression analyses.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Child age even has been shown to influence services offered in schools (i.e., which classroom-based strategies and school-based treatments; Hess, Morrier, Heflin, & Ivey, 2008). A large-scale study of Medicaid-eligible U.S. children indicated that services used change with age: as children got older psychotropic medication increased, while use of speech, occupational, and physical therapies decreased (Cidav, Lawer, Marcus, & Mandell, 2013). Psychopharmacological treatments are consistently reported as more commonly used among older children with ASD (Aman et al, 2003;Goin-Kochel et al, 2007), although drug treatments are increasingly offered to younger and younger children (Olfson, Crystal, Huang, & Gerhard, 2010).…”
Section: Child Age and Treatment Selectionmentioning
confidence: 99%
“…Similar to children with ASD, adults with ASD also have very high healthcare needs (Cidav et al, 2013; Howlin et al, 2004; Lunsky et al, 2009; Mukaetova-Ladinska et al, 2012). A paucity of trained mental health professionals and facilities for optimum management of ASD cases (Mauch et al, 2011), consistent physician reports of lack of self-perceived competency and knowledge in treating adults with ASD (Bruder et al, 2012; Golnik et al, 2009; Miller, 2015; Oskoui and Wolfson, 2012), and no clarity on adult ASD treatment guidelines creates complexities in healthcare delivery which could possibly lead to frequent and excessive healthcare services use and high costs among this group.…”
Section: Introductionmentioning
confidence: 99%